Analisis Hukum terhadap Dominasi Ekonomi Digital: Potensi Monopoli oleh Danantara sebagai Holding BUMN Digital - Muhammad Wildan Ichsandi; Wilma Silalahi (Jurnal Hukum Lex Generalis, 2024)
This study aims to analyze the potential monopoly practices of Danantara as Indonesia’s state-owned digital superholding from the perspective of competition law. The research method employed is normative juridical, using statutory and secondary legal sources. The formation of Danantara as the primary manager of major SOE assets risks creating market dominance and hindering fair competition. The excessive concentration of economic power may reduce competitiveness and limit market access for private actors, potentially violating principles of justice and legal certainty. Although Danantara aims to accelerate economic growth and redistribute wealth, its ownership structure and weak oversight mechanisms raise public concerns over potential corruption and mismanagement. Law No. 5 of 1999 on the Prohibition of Monopolistic Practices serves as a crucial tool to assess the legality of such dominance. Therefore, legal structuring and oversight must be implemented transparently and accountably to prevent market distortion. In conclusion, the government must establish clear authority limits and strengthen regulatory supervision to ensure Danantara’s strategic role aligns with fair competition principles.